Coordinated expression of the renin–angiotensin genes in the lumbar spinal cord: Lateralization and effects of unilateral brain injury. (16th July 2021) - Bakalkin, Georgy; Kahle, Anika; Sarkisyan, Daniil; Watanabe, Hiroyuki; Lukoyanov, Nikolay; Carvalho, Liliana S.; Galatenko, Vladimir; Hallberg, Mathias; Nosova, Olga
Abstract: In spite of its apparent symmetry, the spinal cord is asymmetric in its reflexes and gene expression patterns including leftward expression bias of the opioid and glutamate genes. To examine whether this is a general phenomenon for neurotransmitter and neurohormonal genes, we here characterized expression and co‐expression (transcriptionally coordinated) patterns of genes of the renin–angiotensin system (RAS) that is involved in neuroprotection and pathological neuroplasticity in the left and right lumbar spinal cord. We also tested whether the RAS expression patterns were affected by unilateral brain injury (UBI) that rewired lumbar spinal neurocircuits. The left and right halves of the lumbar spinal cord were analysed in intact rats, and rats with left‐ or right‐sided unilateral cortical injury, and left‐ or right‐sided sham surgery. The findings were (i) lateralized expression of the RAS genes Ace, Agtr2 and Ren with higher levels on the left side; (ii) the asymmetry in coordination of the RAS gene expression that was stronger on the right side; (iii) the decay in coordination of co‐expression of the RAS and neuroplasticity‐related genes induced by the right‐side but not left‐side sham surgery and UBI; and (iv) the UBI‐induced shift to negative regulatory interactions between RAS and neuroplasticity‐related genes on the contralesional spinal side. Thus, the RAS genes may be a part of lateralized gene co‐expression networks and have a role in a side‐specific regulation of spinal neurocircuits. Abstract : The renin–angiotensin system (RAS) genes may be a part of lateralized gene co‐expression networks in the lumbar spinal cord. Expression of three RAS genes is higher on left side, whereas coordination of the RAS gene expression was stronger on right side. Right‐ but not left‐side brain injury and sham surgery impaired coordination between RAS and neuroplasticity gene expression, and the brain injury shifted interactions of these gene groups to negative mode on the contralesional spinal side.